Case Report: Precision Medicine Target Revealed by In Vitro Modeling of Relapsed, Refractory Acute Lymphoblastic Leukemia From a Child With Neurofibromatosis - Heatley, Susan L.; Page, Elyse C.; Eadie, Laura N.; McClure, Barbara J.; Rehn, Jacqueline; Yeung, David T.; Osborn, Michael; Revesz, Tamas; Kirby, Maria; White, Deborah L. (Frontiers in Oncology, 2022)
Children with neurofibromatosis have a higher risk of developing juvenile myelomonocytic leukemia and acute myeloid leukemia, but rarely develop B-cell acute lymphoblastic leukemia (B-ALL). Through in-vitro modeling, a novel NF1 p.L2467 frameshift (fs) mutation identified in a relapsed/refractory Ph-like B-ALL patient with neurofibromatosis demonstrated cytokine independence and increased RAS signaling, indicative of leukemic transformation. Furthermore, these cells were sensitive to the MEK inhibitors trametinib and mirdametinib. Bi-allelic NF1 loss of function may be a contributing factor to relapse and with sensitivity to MEK inhibitors, suggests a novel precision medicine target in the setting of neurofibromatosis patients with B-ALL.